Moderated Mediation of Capital Structure and Company Value by Asset Utilization and Financial Distress - Tri Hijrah Saputro; Akhmadi Akhmadi; Wawan Ichwanudin (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study examines the moderated mediation effects between capital structure and company value using asset utilization as the moderating variable and financial stress as the mediating variable. The study uses the Hayes PROCESS macro model 14 with SPSS Statistics 27 version, and it uses a sample size of 40 observations from 8 enterprises listed in the Software and IT Services subsector on IDX between 2019 and 2023. The capital structure has a direct beneficial impact on firm value. There is no mediation of the link between leverage and firm value by asset utilization. The link between asset usage and business value can be moderated by financial distress, but the indirect impact of leverage on firm value through asset use is not much mitigated by financial distress. These results emphasize the dependent impacts of financial crisis on operational efficiency and business valuation while showing the complex function of leverage in boosting corporate value. They also partially align with the trade-off theory and pecking order theory.